EKSPLORASI PEWARNA DAN MOTIF ALAM PADA KAIN SUTERA DARI VEGETASI HUTAN: Exploration of Natural Colors and Motives on Silk of Forest Vegetation - Sitti Nuraeni; Dewi Fortuna Wahab; Nurfadilah Latif; Nirmala Armidha (Forestry Faculty of Universitas Hasanuddin, 2020)
Natural coloring and batik techniques by directly printing the shape or motifs of leaves, flowers or fruit, called ecoprint, have been in great demand by the global community. Therefore, the search for types of plants that can produce color continues to be pursued. In this study, the aim of this research is to explore the types of plants from the tree level to the understorey which can provide distinctive colors and motifs to silk fabrics. Part of the plant is collected, especially the leaves, flowers and other parts, especially those that have color and can be perfectly expressed on the fabric. The coloring method used is direct paste method or better known as ecoprint. The mordant treatment used was basic mordant, namely the treatment of soaking the cloth in 10 g / l alum solution for 24 hours. The plant part samples were treated with immersion for 12 hours in 10 g of alum solution plus 30 g of acetic acid. Next, the plant samples are laid out on a cloth and wrapped in clear heat-resistant plastic. After the cloth is wrapped and tied tightly so that it sticks tightly and does not blend in the colors, then steam it for 2 hours. The results of this study showed that of the 88 plant species tested, only 32 species produced the expression of their color and motif from the leaf part, while in flowers there were only two types and one sample from the fruit part. The data from this research can provide information for silk craftsmen as an alternative choice of natural dyes and motifs for fabrics.